Community Service Program for Tuna Fishermen's Group in East Dumai Subdistrict, Dumai City - Yogia, Moris Adidi; Wedayanti, Made Devi; Prihatin, Panca Setyo; Pulungan, Boby Indra; Lestari, Meilan; Febriana, Winda; Azzani, Alfia Umaira (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to address administrative challenges within the Tuna Fishermen's Group in Dumai City, including manual record-keeping, reliance on external administrative support, damaged fishing equipment, and the group's inability to develop CSR proposals for additional funding.Method: The study used a community service approach (PKM) that involved socialization, provision of administrative tools and fishing equipment, educational workshops, and training. An evaluation was conducted to assess the program's effectiveness.Practical Applications: The findings can help improve the fishermen's administrative practices, reduce external dependency, enhance equipment management, and guide them in securing CSR funding for sustainability.Conclusion: The PKM activities were well-implemented and supported by the Tuna Fishermen's Group, leading to improved operational efficiency and addressing the group's key issues.